2016
DOI: 10.1016/j.watres.2016.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community adaptation influences long-chain fatty acid conversion during anaerobic codigestion of fats, oils, and grease with municipal sludge

Abstract: Codigesting fats, oils, and greases with municipal wastewater sludge can greatly improve biomethane recovery at wastewater treatment facilities. Process loading rates of fats, oils, and greases have been previously tested with little knowledge of the digester microbial community structure, and high transient fat loadings have led to long chain fatty acid (LCFA) accumulation and digester upsets. This study utilized recently-developed quantitative PCR assays for syntrophic LCFA-degrading bacteria along with 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 53 publications
2
52
0
1
Order By: Relevance
“…S3). Higher concentrations of Syntrophomonas have previously been correlated with higher degradation rates of LCFA in anaerobic digestion (Ziels et al ., , , ). Recently, 16S rRNA gene expression of Syntrophomonas was correlated with methane production from LCFA‐rich waste (Amha et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…S3). Higher concentrations of Syntrophomonas have previously been correlated with higher degradation rates of LCFA in anaerobic digestion (Ziels et al ., , , ). Recently, 16S rRNA gene expression of Syntrophomonas was correlated with methane production from LCFA‐rich waste (Amha et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, resilience was found to be an important factor in maintaining a syntrophic population exposed to disturbances in a full-scale reactor, where syntrophs rebounded following stress conditions (Werner et al, 2011). Another study also suggested reversibility of LCFA inhibition due to an increase in relative abundance of syntrophic β-oxidizing bacteria, primarily Syntrophomonas (Ziels et al, 2016). Further, the same study reported that the abundance and composition of methanogens was unaffected by addition of 100-1570 mg oleic acid g VS −1 , where 70% of the methanogens were hydrogenotrophic (Methanomicrobiales) and 30% were acetoclastic (Methanosaeta).…”
Section: Syntrophy and Methanogenesismentioning
confidence: 93%
“…Although fatty acid-based inhibition is not well understood, researchers have identified several likely mechanisms of inhibition: disruption of the electron transport chain and oxidative phosphorylation, interference with cellular energy production, direct lysis of bacterial cells, and decreased cell permeability (Desbois and Smith, 2010;Pereira et al, 2005). However, some studies have suggested that LCFA inhibition is reversible Pereira et al, 2005;Ziels et al, 2016). For example, a study involving cattle manure digestion with the addition of sodium oleate to simulate high LCFAs reported that the perturbation observed was reversible .…”
Section: Syntrophy and Methanogenesismentioning
confidence: 99%
“…Dewatering ability of the stabilised SS proceeded with a fluctuating pattern throughout the study with a limited improvement at the highest VLRs (0.44 and 0.57 kg VS/(m 3 •d)) indicating that lower HRT, thus, lower destruction of SS, may require a lower chemical/polymer consumption at the decanter unit than lower VLRs/higher HRT. High oil and grease content is known to affect stabilised sludge dewaterability and beneficial usage in a negative direction (Ziels et al, 2016). Reduction in filtering time in stabilised PS to lower levels than stabilised SS was correlated to efficient removal of oil and grease.…”
Section: Dewaterabilitymentioning
confidence: 95%